Pendidikan Penguatan Karakter Melalui Pembiasaan Akhlak Mulia - Asep Habib Idrus Alawi (Qiro'ah : Jurnal Pendidikan Agama Islam, 2019)
Strengthening of the character education constitute of effort is very important for achieving national education goals. The character of education must be instilled early and will be the main foundation for the formation of national character. Considering importance of character education, educators must make efforts to introduce and develop character of education for students. One form of effort to strengthen the character of students in school is through ways of habituating noble character. This Study purpose to identify about: Program to strengthen character education in elementary schools through the habituation of noble character. This study uses descriptive qualitative methods, data collection is done by observation, interviews, and ocumentation studies. Data analysis was carried out by stages of data inventory, classifying data, analyzing data, and formulating conclusions. The results of this study indicate that: The program for reinforcement of the character education at Adzkia 1 Elementary School Cisaat and Cisaat Public Elementary School in Sukabumi Regency is by integrating the learning process by habituating noble moral values ​​in daily life;